A chamber study of alkyl nitrate production formed by terpene ozonolysis in the presence of NO and alkanes - Jackson, Stephen R.; Harrison, Joel C.; Ham, Jason E.; Wells, J.R. (Atmospheric environment (1994), 2017)
Organic nitrates are relatively long-lived species and have been shown to have a potential impact on atmospheric chemistry on local, regional, and even global scales. However, the significance of these compounds in the indoor environment remains to be seen. This work describes an impinger-based sampling and analysis technique for organic nitrate species, focusing on formation via terpene ozonolysis in the presence of nitric oxide (NO). Experiments were conducted in a Teflon film environmental chamber to measure the formation of alkyl nitrates produced from α-pinene ozonolysis in the presence of NO and alkanes using gas chromatography with an electron capture detector. For the different concentrations of NO and O3 analyzed, the concentration ratio of [O3]/[NO] around 1 was found to produce the highest organic nitrate concentration, with [O3] = 100 ppb & [NO] = 105 ppb resulting in the most organic nitrate formation, roughly 5 ppb. The experiments on α-pinene ozonolysis in the presence of NO suggest that organic nitrates have the potential to form in indoor air between infiltrated ozone/NO and terpenes from household and consumer products. •Description of ethyl acetate as an impinger medium for collection of gas-phase organic nitrates.•Quantified alkyl nitrate formation initiated by terpene ozonolysis for a range of ozone and NO concentrations.•Ozone and NO concentrations near 100 ppb resulted in the highest organic nitrate yield observed, roughly 5 ppb.